Jesus wars : how four patriarchs, three queens, and two emperors decided what Christians would believe for the next 1,500 years - Thikins, Philip, 1952- (New York : HarperOne, 2010)
Jesus Wars reveals how official, orthodox teaching about Jesus was the product of political maneuvers by a handful of key characters in the fifth century. Jenkins argues that were it not for these controversies, the papacy as we know it would never have come into existence and that today's church could be teaching some-thing very different about Jesus. It is only an accident of history that one group of Roman emperors and militia-wielding bishops defeated another faction. --from publisher description.
The heart of the matter -- The war of two natures -- Four horsemen: the Church's patriarchs -- Queens, generals, and emperors -- Not the Mother of God? -- The death of God -- Chalcedon -- How the Church lost half the world -- What was saved.
Includes bibliographical references (p. [289]-317) and index.
Keywords: Jesus Christ -- History of doctrines; Jesus Christ -- Person and offices; Theology, Doctrinal -- History -- Early church, ca. 30-600.; Church history -- Primitive and early church, ca. 30-600.; Councils and synods; Christian civilization